Strategi Guru PAI dalam Menguatkan Karakter Siswa melalui Kegiatan Istighosah Rutin di SDN Wonosari Gempol Pasuruan - Laila Badriyah; Suyeqty Mukarromah; Almeta Hanifah Widiana (Jurnal Keislaman, 2023)
Istighosah is not merely confined to religious practice but also serves as a means to preserve and safeguard the culture and identity of the community as a whole. This inspires a deep understanding of spiritual principles that strengthen and nurture the community in harmony with the embraced local wisdom. This study aims to analyze the strategies of Islamic Education teachers in reinforcing students' character through regular Istighosah activities. Through a phenomenological approach, data was collected through participatory observation, in-depth interviews, and document analysis at SDN Wonosari Gempol, Pasuruan. The collected data were afterward analyzed using the methods developed by Miles Huberman and Saldana (2014), which involve data condensation, data presentation, and conclusion. The study's findings reveal that Islamic Education teachers in Reinforcing Students' Character through Routine Istighosah Activities at SDN Wonosari Gempol Pasuruan reflected that students can exhibit religious attitudes in their daily lives, demonstrate discipline both individually and collectively, and exhibit a sense of responsibility as learners by learners performing their tasks diligently.